Assessment of Combination Approaches of Phytoconstituents with Chemotherapy for the Treatment of Breast Cancer: A Systematic Review - Sartaj, Ali; Baboota, Sanjula; Ali, Javed (Current Pharmaceutical Design, 2021)
Objective: Available conventional therapies are commonly used for the treatment of breast cancer, such as surgical procedures, hormonal therapy, radiation therapy, and chemotherapy. These therapies can be either given alone or in combination with other therapies. Various side effects associated with chemotherapies, including toxicity and multidrug resistance, have limited the use of chemotherapy, thus making it less effective than the above mentioned therapies. This review focus has been summarised as the application of anticancer with phytoconstituents that could be a promising and effective treatment strategy for breast cancer treatment. Methods: This review is designed on relevant literature that was screened on the basis of in-scope criteria in the title, abstract, and keywords of the searched articles. The available literature was searched on PubMed, ScienceDirect, MedlinePlus, and Google scholar up to May 2021. A total of 47 articles were selected out of 168 articles based on inclusion and exclusion criteria. Results: The major limitations accompanying available conventional treatment, mainly chemotherapy, include low bioavailability at the specific site of tumor cells, the occurrence of multidrug resistance, and high doserelated side effects. The phytoconstituents possessing anticancer properties and, when used in combination with chemotherapeutic agents, impart promising and potential therapeutic value. Many in vitro and in vivo studies showed that phytoconstituents could enhance the effectiveness of chemotherapy drugs for breast cancer treatment. Conclusion: The combination approaches of phytoconstituents with chemotherapeutic drugs provide less toxicity to normal cells, reduce side effects, and overcome multidrug resistance, thus making the combination approaches an effective strategy for the treatment of breast cancer.
Keywords: Breast cancer